2010
DOI: 10.1016/j.crte.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution de données climatiques pour l’Algérie du Nord : application des réseaux neuronaux

Abstract: le contexte actuel de changement climatique et de pre ´servation de la biodiversite´, l'appre ´ciation de la vulne ´rabilite ´des e ´cosyste `mes naturels et de leur capacite ´d'adaptation figurent parmi les principales pre ´occupations au niveau mondial (GIEC, 2007). Cette e ´valuation des e ´cosyste `mes ne ´cessite la disponibilite ´de donne ´es climatiques, ce qui est souvent rendu difficile par la faible densite ´voire l'absence de stations me ´te ´orologiques notamment, au niveau des zones de montagnes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The differences can be explained by the nature of the soils of harvest localities. Calcareous soil‐humic rich in organic matter characterized areas 1 and 2 however the vegetation in area 2 is more existing in a climate vegetation (holm oak, Aleppo pine) with a dense undergrowth indicated that soil is rich in bases including Ca ++ , Mg ++ and K + . Rich‐mineral soils seem to further the production of essential oils of M .…”
Section: Resultsmentioning
confidence: 99%
“…The differences can be explained by the nature of the soils of harvest localities. Calcareous soil‐humic rich in organic matter characterized areas 1 and 2 however the vegetation in area 2 is more existing in a climate vegetation (holm oak, Aleppo pine) with a dense undergrowth indicated that soil is rich in bases including Ca ++ , Mg ++ and K + . Rich‐mineral soils seem to further the production of essential oils of M .…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of research is challenging in this context. Our results imply that the prevalence identified in this study may be associated with suitable climatic conditions, because the four study provinces (Mila, Constantine, Guelma, and El Taref) have similar ecological patterns characterized by a wet period during most of the year [ 22 ] that are favorable for T. gondii oocyst formation and survival [ 5 ]. As a result, this region in Algeria has the greatest prevalence rate of the parasite in animals [ 21 ].…”
Section: Discussionmentioning
confidence: 96%
“…The region has a humid Mediterranean climate, with hot, dry summers and cold, wet winters. The annual rainfall is approximately 550 mm with a relative humidity of 70%, and the annual temperature varies between 8 °C and 24 °C [ 22 ]. Constantine is situated on a plateau at 698 m above sea level; the area has a humid climate with hot, dry summers and cold, moist winters and is characterized by an annual rainfall of 600 mm, an annual temperature range of 10 °C to 25 °C, and 60% annual relative humidity [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations